The Effect of Board Composition, Audit Report Lag, Auditor Switching, Audit Committee and Audit Tenure on Audit Quality - Rifany, Risty; Trisnawati, Rina; Kholillulloh, Fajar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: To examine the effect of board composition, audit report lag, auditor switching, audit committee and audit tenure on audit quality in companies listed on the Indonesia Stock Exchange. This research is based on several findings of cases of embezzlement of funds and taxes that have occurred in several metal subsector companies and the like, related to the low quality of the resulting financial statements. Methodology: The method used in this research is the quantitative method. The population in this study imcluded manufacturing companies in the metal subsector and the like listed on the IDX in 2019-2023. The sampling technique used in this research is the saturated sampling technique, and the final result of the data sample is 85. The data analysis method uses SPSS software to test the logistic regression analysis method. Results: Based on the results of the analysis using the dummy method, it is concluded that the board composition variable, audit report lag, and audit committee have a significant effect on audit quality, while the auditor switching variable and audit tenure have no significant effect on audit quality. Applications/Originality/Value: The results of this study are hoped to provide benefits to auditors, company management, and the scientific field because this research discusses and provides recommendations on what factors can affect audit quality. As well as this understanding can be used as a recommendation for improving performance and corporate governance. this research is a development of previous research with updated independent variables on board composition and audit committee. From the results of the literature review, it is found that there are still few studies that discuss the impact of board composition on audit quality by measuring the number of boards of directors in the company.